Protein and gene delivery systems for neurodegenerative disorders: Where do we stand today? - Siafaka, Panoraia I.; Okur, Mehmet Evren; Dilsiz Erim, Pelin; Çağlar, Emre Şefik; Özgenç, Emre; Gündoğdu, Evren; Parlar Köprülü, Rabia Edibe; Karantaş, Ioannis D.; Üstündağ Okur, Neslihan (MDPI, 2022)
It has been estimated that every year, millions of people are affected by neurodegenerative disorders, which complicate their lives and their caregivers’ lives. To date, there has not been an approved pharmacological approach to provide the complete treatment of neurodegenerative disorders. The only available drugs may only relieve the symptoms or slow down the progression of the disease. The absence of any treatment is quite rational given that neurodegeneration occurs by the progressive loss of the function or structure of the nerve cells of the brain or the peripheral nervous system, which eventually leads to their death either by apoptosis or necrotic cell death. According to a recent study, even though adult brain cells are injured, they can revert to an embryonic state, which may help to restore their function. These interesting findings might open a new path for the development of more efficient therapeutic strategies to combat devastating neurodegenerative disorders. Gene and protein therapies have emerged as a rapidly growing field for various disorders, especially neurodegenerative diseases. Despite these promising therapies, the complete treatment of neurodegenerative disorders has not yet been achieved. Therefore, the aim of this review is to address the most up-to-date data for neurodegenerative diseases, but most importantly, to summarize the available delivery systems incorporating proteins, peptides, and genes that can potentially target such diseases and pass into the blood–brain barrier. The authors highlight the advancements, at present, on delivery based on the carrier, i.e., lipid, polymeric, and inorganic, as well as the recent studies on radiopharmaceutical theranostics.
Keywords: Genes; Monoclonal Antibodies; Neurodegenerative Diseases; Peptides; Protein; Theranostics